INVESTIGATING AWARENESS AND EDUCATIONAL GAPS CONCERNING EMOTIONAL BURNOUT SYNDROME AMONG HEALTHCARE PROFESSIONALS - Ivashchenko, R.O.; Nesterenko, V.G. (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2025)
Introduction. Burnout syndrome is a professional phenomenon that occurs as a result of chronic stress at the workplace, if the stress has not been successfully overcome. In 2019, the World Health Organization included burnout syndrome in the 11th edition of the International Classification of Diseases (ICD-11) as a condition characterized by three main symptoms: a feeling of exhaustion, mental detachment from work, and decreased professional effectiveness. Objective. This study is devoted to examining the level of awareness among medical workers regarding emotional burnout syndrome, the sources of information about this phenomenon, and the analysis of prevention practices among representatives of the medical field. Its purpose is also to identify the extent of knowledge on the issue of emotional burnout syndrome, the accessibility of reliable information for medical workers, and the development of recommendations for improving the psycho-emotional state of specialists. This study also focused on identifying the main resources for obtaining knowledge about this syndrome, participation in preventive measures, and determining the need for detailed information on this topic. Material and methods. Sociological and mathematical-statistical methods were used in this work. The research tools included a questionnaire on the level of awareness on the issues of emotional burnout syndrome, sources of information, and preventive measures. Results and conclusion. The findings obtained established that despite the fact that 100% of respondents were aware of emotional burnout syndrome, only 18.9% of them rated their level of knowledge as high, 53.2% as average, and 27.9% as low. The definitions of the syndrome provided by the respondents were mostly consistent with the basic characteristics of the phenomenon, but demonstrated a lack of systematic understanding. The vast majority of respondents (61.5%) receive information about emotional burnout syndrome from unreliable sources such as internet platforms and social networks, and only 5.0% from professional literature. Referring to preventive measures, 46.2% of respondents have no knowledge of methods for preventing emotional burnout.